If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8=2(h+1)
We move all terms to the left:
8-(2(h+1))=0
We calculate terms in parentheses: -(2(h+1)), so:We get rid of parentheses
2(h+1)
We multiply parentheses
2h+2
Back to the equation:
-(2h+2)
-2h-2+8=0
We add all the numbers together, and all the variables
-2h+6=0
We move all terms containing h to the left, all other terms to the right
-2h=-6
h=-6/-2
h=+3
| 8x-16=6x+2 | | Y=-6x^2-24 | | (2+3x)(4-x)=3x(3-x) | | 2=n-6/2 | | 13x-20x=1/3 | | 8g=8+10g | | 2y^2-7=0 | | -1-7f=5-9f | | 7-6s=-5-6s | | 3k+6=4k | | 12z=10z+20-12 | | 12x-7x=2x+5 | | 7=7+1/10t | | -6x+6(2x+-3)=-5-7x | | 0.2/b=20 | | -4m+3m=3/2 | | x^2+(x–4)^2=20^2 | | 3y^2-11y+12=0 | | 9(2e+1)-3(e-2)=45 | | (x+-8)^4=16 | | -5j=4j-9j | | x^2+13+24=0 | | -q+10=5q-8 | | 9×(x-2)=3x×(x-2) | | 3n-1=3n | | 9(x-1)=90 | | x+√4x+1=5 | | 7(3x-1)/4=-14 | | 2z-4=2z+3 | | 4(2u+8)=5(u+4) | | 7(3x-1)=-14 | | -4c=6c-10 |